Expressão heterológa, purificação e caracterização estrutural do peptídeo (171-194) da p24 do HIV-1 - Castilho, Priscila Vasques (2004)
Proteins from the inner core of HIV-1 are involved in crucial processes during the virus life cycle. p24 is the major capsid protein of HIV and is initially expressed as part of the gag polyprotein. The association of gag proteins to the cell inner-membrane surface initiates virus assembly and induces budding from the host cell membrane. Thus, p24 plays an active structural role both as part of the Gag protein and in its mature form. In this sense, we have chosen a region from C-terminal of p24, TLRAEQASQEVKNWMTETLLVQNA, (p24-3) which is part of the major region responsible for protein dimerization. The linear peptide, rp24-3, and its cyclic variant, rp24-3m, were produced by recombinant strategy in Escherichia coli. The gene fragments were obtained by the synthetic gene approach and inserted into pET 32a to produce fusion proteins in the soluble form. The expression products were purified by Ni-affinity chromatography followed by an enzymatic cleavage. The peptides where purified by reverse phase chromatography and their primary sequence and molecular masses where inferred by amino acid sequence analysis and mass spectrometry, respectively. The rp24-3 secondary structure was investigated by circular dichroism and steady state fluorescence, been structured differently in water and in buffer. Besides, its tryptophan is in a partially buried environment and the addition of methanol above 70% caused a highly increase in helical content. In conclusion, this work shows a suitable system for rp24-3 production, providing satisfactory amount for structural studies.